2011
DOI: 10.1093/ije/dyr152
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological methods in diarrhoea studies—an update

Abstract: Background Diarrhoea remains a leading cause of morbidity and mortality but is difficult to measure in epidemiological studies. Challenges include the diagnosis based on self-reported symptoms, the logistical burden of intensive surveillance and the variability of diarrhoea in space, time and person.Methods We review current practices in sampling procedures to measure diarrhoea, and provide guidance for diarrhoea measurement across a range of study goals. Using 14 available data sets, we estimated typical desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 81 publications
1
119
1
Order By: Relevance
“…Although caregiver-reported illness could be subject to under-reporting, 27 we validated the community-based diarrhea surveillance with clinic records in the study villages. 25 With respect to water quality analysis, we conducted a few initial side-by-side comparisons of our total coliform and E. coli diagnostics with Coliscan membrane filter medium (Micrology Laboratories CMFK2; Micrology Laboratories, Goshen, Indiana).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although caregiver-reported illness could be subject to under-reporting, 27 we validated the community-based diarrhea surveillance with clinic records in the study villages. 25 With respect to water quality analysis, we conducted a few initial side-by-side comparisons of our total coliform and E. coli diagnostics with Coliscan membrane filter medium (Micrology Laboratories CMFK2; Micrology Laboratories, Goshen, Indiana).…”
Section: Discussionmentioning
confidence: 99%
“…The primary health outcome in this study was caregiver-reported diarrhea during the 7 days before the visit among children 5 years of age at enrollment; we defined diarrhea as three or more loose or watery stools in 24 hr or a single stool with blood or mucus. 26,27 Field interviewers collected caregiver-reported symptoms during each monthly home visit with the aid of a health calendar. 28 Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…12 Although many epidemiological studies use survey-reported diarrhea as a dependent variable, we make no attempt to study this noisy and unreliable outcome measure (Schmidt et al, 2011). For example, Zwane et al (2011) show that households randomly selected to be surveyed more frequently report less child diarrhea.…”
mentioning
confidence: 99%
“…To measure the exact burden of AGI by means of epidemiological studies is a demanding task (2). Assessments of disease burden are often based on singular health metrics such as incidence, prevalence or mortality data alone (3).…”
Section: Introductionmentioning
confidence: 99%